2013
DOI: 10.1371/journal.pone.0067467
|View full text |Cite
|
Sign up to set email alerts
|

Powdery Mildew Resistance in Tomato by Impairment of SlPMR4 and SlDMR1

Abstract: Genetic dissection of disease susceptibility in Arabidopsis to powdery and downy mildew has identified multiple susceptibility (S) genes whose impairment results in disease resistance. Although several of these S-genes have been cloned and characterized in more detail it is unknown to which degree their function in disease susceptibility is conserved among different plant species. Moreover, it is unclear whether impairment of such genes has potential in disease resistance breeding due to possible fitness costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(119 citation statements)
references
References 26 publications
4
107
0
Order By: Relevance
“…We are currently verifying whether silencing tomato orthologs of these Arabidopsis S-genes leads to resistance to O. neolycopersici. Our results till now showed that (1) Arabidopsis dmr1 and pmr4 mutants are resistant to O. neolycopersici and, (2) silencing SlDmr1 and SlPmr4 in tomato results also in resistance to O. neolycopersici (Huibers et al 2013). Together with the tomato ol-2 mutant (Slmlo1), our results demonstrate that orthologs of Arabidopsis S-genes are present in crops and disruption in their S-gene function leads to resistance to different pathogens.…”
Section: Nonhost-like Resistance Conferred By Editing Plant S-genessupporting
confidence: 53%
“…We are currently verifying whether silencing tomato orthologs of these Arabidopsis S-genes leads to resistance to O. neolycopersici. Our results till now showed that (1) Arabidopsis dmr1 and pmr4 mutants are resistant to O. neolycopersici and, (2) silencing SlDmr1 and SlPmr4 in tomato results also in resistance to O. neolycopersici (Huibers et al 2013). Together with the tomato ol-2 mutant (Slmlo1), our results demonstrate that orthologs of Arabidopsis S-genes are present in crops and disruption in their S-gene function leads to resistance to different pathogens.…”
Section: Nonhost-like Resistance Conferred By Editing Plant S-genessupporting
confidence: 53%
“…Two S-genes for downy mildew, DMR1 and DMR6, have been described in Arabidopsis and tomato [12,[19][20][21]. dmr1 and dmr6 mutants induce resistance to DM by accumulating elevated levels of homoserine [21] and 2OG-Fe(II) oxygenase [20], respectively.…”
Section: Journal Of Phylogenetics and Evolutionary Biologymentioning
confidence: 99%
“…Therefore, a loss of function in MLO genes consequently induce resistance to PM [10,15]. PMR genes on the other hand are far less studied and most are putative, but some have been shown to play a role in PM susceptibility in Arabidopsis (AtPMR4, AtPMR5, and AtPMR6) and tomato (SlPMR4) [16][17][18][19]. PMR genes are involved in cell wall biology where they mediate structure formation and pectin accumulation [18].…”
Section: Introductionmentioning
confidence: 99%
“…We collected peroxidase gene (AY373372; García-Gutiérrez et al 2013) and Arabidopsis Powdery Mildew Resistant 4 (PMR4) gene encoding callose synthase (protein AEE82336.1; Huibers et al 2013) from the literature. Then we blasted these two gene sequences in the Melon Genome Database 'Melonomics' (https://melonomics.net/) and retrieved two peroxidases (Prx) and one glucan synthase (GLS)-like genes.…”
Section: In Silico Analysis Of Peroxidase and Glucan Synthase-like Genesmentioning
confidence: 99%